Experience report: implementation of a multi‐standard compliant process improvement program. Issue 5 (24th July 2013) - Kaynak, Onur; Karagöz, N. Alpay; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
Abstract This paper explains the experience of an information technology (IT) solutions provider company about the integrated management of the International Organization for Standardization (ISO)/International Electrotechnical Commission (IEC) 15504 based process assets library with other related IT standards, which are ISO/IEC 27001, ISO/IEC 20000, and ISO 9001:2008. In order to establish and execute an efficient and effective infrastructure, a companywide process improvement program has been conducted. The lessons that are learned from the execution of this process improvement program, key implementation, practices and major challenges are shared in this paper. Copyright © 2013 John Wiley & Sons, Ltd.